The Ac Conductivity Of Samarium Phosphate Glasses - Ngasmin, Agus Setyo Budi; Ahmad, Asmala; Ayof, Mohamad Nizam; Lau, Kok Tee (2006)
The ac conductivity of o,, samarium phosphate glasses with different Sm2O3 content is measured in frequency range of 10' to 10' Hz over the temperature range of 300 to 553 K. The observed frequency dependence can be expressed as o,,= Am ' , where 0.6 < s < 1 which confirms the electron hopping phenomena. The bulk conductivity increases with increasing temperature and decreases with the increasing neodymium content.